Determinant Factors Correlate with the Selection of Contraceptive Intra Uterine Device (IUD) - Rizki Apriliani Fadzilah; Bekti Yuniyanti; Masini Masini (Midwifery and Nursing Research, 2019)
Background: The direction of national policies and strategies for the 2015-2016 period focused on improving family planning services by using Long Term Method to reduce risks to drop out. IUD is one of contraception with no hormonal side effect. IUD is a contraceptive device or small object inserted into the uterus that can be used for all women of reproductive age.Purpose: The purpose of this study to determine the economic factors, attitudes and support of husbands that affect the election of contraceptive IUD in the work area Puskesmas Mungkid, Magelang District.Methods: cross sectional design by using purposive sampling technique were applied. Univariate analysis to know the frequency distribution of each variable. Bivariate analysis using chi-square test for economic relations test, attitude, husband  support with election planning. Multivariate analysis using logistic regression test to test the influence of economy, attitude and support of husband to IUD election.Results: Based on the results of the study, most respondents have less than the minimum wage of 71.7%, there are 53.3% of respondents have a negative attitude towards IUD, and 51.7% of respondents have husband support. of respondents who chose to use IUD as much as 16.7%. In the chi-square test, there is a relationship of attitude with the election of IUD (p value 0.004).Conclusion: Based on the result of the research, it is hoped that the mother can improve the mother's attitude toward IUD by improving the mother's knowledge through information.